Microscopic investigations and pharmacognostic techniques used for the standardization of herbal drug Nigella sativa L. Issue 12 (23rd October 2018) - Rashid, Sofia; Zafar, Muhammad; Ahmad, Mushtaq; Lone, Farooq Ahmad; Shaheen, Shabnum; Sultana, Shazia; Ashfaq, Shomaila; Shinwari, Muhammad Ibrar
Abstract: A comprehensive account on standardization of herbal drug Nigella sativa L. (Tukhm‐e‐Kalonji) by using microscopic as well as pharmacognostic parameters. In the field of herbal medicines, the main issues are quality, purity, and effectiveness, as in many cases herbal drugs are knowingly or unknowingly substituted or adulterated with similar species or varieties. In herbal market the seeds of N. sativa are commonly adultered with seeds of Allium cepa L. intentionally or accidentally due to their similar morphology. In the present study, the microscopic characterization of herbal drug was done by morphological, palynological, and anatomical features. A great diversity was found in anatomical features of two species, as irregular epidermal cells, actinocytic stomata, and nonglandular trichomes were found in N. sativa while in A. cepa epidermal cells were rectangular in shape, stomata type was paracytic, and trichomes were absent. Pharmacognostic characterization was made by fluorescence analysis and physiochemical parameters. Physicochemical parameters like moisture content, total ash, acid insoluble ash, water soluble ash, and water insoluble ash were also evaluated. The above parameters, being reported to the first time for the studied plant species, and are significant towards establishing the microscopic and pharmacognostic standards for future identification and authentication of genuine herbal drug. Research highlights: Microscopic Investigations for the standardization of herbal drug Nigella sativa L. (Tukhm‐e‐Kalonji). Pharmacognostic techniques are potentially significant for the standardization of herbal drug Nigella sativa in comparison with its adulterant. Useful for preparation of standards for herbal pharmacopeia. Abstract :